2017
DOI: 10.7287/peerj.preprints.3172v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive phylogenomic analyses resolve cnidarian relationships and the origins of key organismal traits

Abstract: Background: The phylogeny of Cnidaria has been a source of debate for decades, during which nearly all-possible relationships among the major lineages have been proposed. The ecological success of Cnidaria is predicated on several fascinating organismal innovations including symbiosis, colonial body plans and elaborate life histories, however, understanding the origins and subsequent diversification of these traits remains difficult due to persistent uncertainty surrounding the evolutionary relationships withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
3
10
1
Order By: Relevance
“…These species designations, which are based on kimura 2-parameter pairwise distance, fall within previous estimations for other scyphozoans, ranging from 0.00 to 0.034 for conspecifics, and 0.102-0.234 for congenerics (Holland et al, 2004;Ortman et al, 2010;Gómez Daglio and Dawson, 2017). Analyses with expanded taxon sampling (Bayha et al, 2010;Kayal et al, 2013Kayal et al, , 2017 have placed the monogeneric Cassiopea within the family Cassiopeidae, in an unstable position within the clade Kolpophorae, along with representatives of Mastigiidae, Thysanostomatidae, Versurigidae, and Cepheidae (Figure 2). The Kolpophorae belongs to the order Rhizostomeae, a well-supported clade derived from within the scyphozoan order Semaeostomeae (Bayha et al, 2010;Kayal et al, 2013).…”
Section: Evolution and Phylogeneticssupporting
confidence: 79%
See 1 more Smart Citation
“…These species designations, which are based on kimura 2-parameter pairwise distance, fall within previous estimations for other scyphozoans, ranging from 0.00 to 0.034 for conspecifics, and 0.102-0.234 for congenerics (Holland et al, 2004;Ortman et al, 2010;Gómez Daglio and Dawson, 2017). Analyses with expanded taxon sampling (Bayha et al, 2010;Kayal et al, 2013Kayal et al, , 2017 have placed the monogeneric Cassiopea within the family Cassiopeidae, in an unstable position within the clade Kolpophorae, along with representatives of Mastigiidae, Thysanostomatidae, Versurigidae, and Cepheidae (Figure 2). The Kolpophorae belongs to the order Rhizostomeae, a well-supported clade derived from within the scyphozoan order Semaeostomeae (Bayha et al, 2010;Kayal et al, 2013).…”
Section: Evolution and Phylogeneticssupporting
confidence: 79%
“…Of particular note, all Cassiopea life stages show telomerase activity, with potential elongation of the telomere during the medusa stage (Ojimi et al, 2009;Ojimi and Hidaka, 2010), paving the way for additional research in the genetic mechanisms of regeneration and longevity in non-bilaterian organisms. Future research in Cassiopea development incorporating genomics, transcriptomics, metabolomics, and in situ hybridization will FIGURE 2 | A working hypothesis of Medusozoa phylogeny based on several studies (Bayha et al, 2010;Kayal et al, 2013Kayal et al, , 2017, including the monophyletic Scyphozoa, Rhizostomeae, Kolpophorae, and Cassiopeidae. Principal morphological and life cycle characters are plotted on the tree (1, cnidae; 2, medusa stage; 3, rhopalia; 4, strobilation, and ephyra; 5, monodisc strobilation).…”
Section: Life Historymentioning
confidence: 99%
“…Despite consistent support for these three major groups in the literature, relationships within each are still contentious, and differences within Medusozoa in particular could impact our ancestral state estimations. Our analyses consistently place Staurozoa as sister to other medusozoan groups as suggested previously by rDNA analyses [10] but in disagreement with recent phylogenomic studies [11,12]. However, differences in the phylogenetic relationships within medusozoan groups (especially within Hydrozoa) did not affect our conservative inference of at least eight origins of eyes in Cnidaria (see supplemental results in Data and Software Availability in STAR Methods).…”
Section: Phylogenetic Support For Multiple Origins Of Eyes Among Adulcontrasting
confidence: 63%
“…Recent systematics studies have directly challenged taxonomic relationships at all levels. A mitogenomic analysis recently challenged the placement of the order Coronatae, such as Periphylla , within Scyphozoa ( Kayal et al, 2013 ; but see Kayal et al, 2017 ) and the new family Drymonematidae was created based on morphological, molecular, and life history data ( Bayha & Dawson, 2010 ; Bayha et al, 2010 ). Studies employing molecular and/or morphological data have revealed novel species in multiple scyphozoan genera, including the moon jellyfish Aurelia ( Dawson & Jacobs, 2001 ; Schroth et al, 2002 ; Dawson, 2003 ), the genus Drymonema ( Bayha & Dawson, 2010 ), the upside down jellyfish Cassiopea ( Holland et al, 2004 ), and the lion’s mane jellyfish Cyanea ( Dawson, 2005 ; Kolbasova et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%